The privacy right and right to be forgotten: the Malaysian perspectives - Mohamed, Duryana (World Academy of Research in Science and Engineering (WARSE), 2016)
Privacy right is a fundamental right recognised by the 1948 United Nation Declaration of Human Rights (UNDHR), the International Convenant on Civil and Political Rights (ICCPR) and in many other international and regional treaties. While right to be forgotten (RTBF) was recognised in 2014 when the European Court of Justice (EUCJ) made a decision in the case of Google Spain SL, Google Inc. v Agencia Española de Protección de Datos, Mario Costeja González. The RTBF allows the Internet users to erase any information about themselves such as their personal information by making request to the Internet Service Provider or data processor to remove the information from the websites. Following the above court decision, many have argued that it shall not be implemented while some others have agreed to this new concept of right under the privacy law. The issue arises when certain countries such as Malaysia do not have a specific privacy law to adopt and implement such right. Hence, this paper examines the right to privacy and its position in Malaysia, its relevancy to right to be forgotten and whether RTBF shall be adopted in Malaysia. For background information reference is made to the privacy laws and the position of RTBF in few other countries. Keywords- Privacy, data protection, right to be forgotten, personal information